The influence of work discipline on the performance of PT employees. at griya pratama (yomart) garut city 35 area - Paroli (International Journal on Social Science, Economics and Art, 2024)
This research aims to evaluate the influence of discipline on employee performance at PT. Griya Pratama (YOMART) Garut City Region 35. The research method used was quantitative using SPSS version 26 statistical tools. Respondents consisted of 41 employees from 6 Yomart stores branch 35 Garut City who filled out a questionnaire as a data source. The results of the analysis show that there is a significant relationship between the level of work discipline and employee performance, with a correlation coefficient of 0.768, indicating a strong relationship. Work discipline can explain around 58.9% of the variation in employee performance, with the remaining 41.1% influenced by other factors not studied. Hypothesis testing confirms the significant influence of work discipline on employee performance, with a significance value of 0.000 < 0.05. Thus, it can be concluded that the implementation of work discipline has a positive effect on employee performance achievement at PT. Griya Pratama (YOMART) Garut City Region 35. This conclusion provides a basis for company management to consider strategies for improving work discipline culture in order to achieve optimal performance from its human resources. The implication is that work discipline has a key role in achieving organizational goals and increasing the company's competitiveness amidst competitive market dynamics.